MODERN INSTITUTION OF HIGHER EDUCATION AS A SCIENTIFIC AND INNOVATIVE CENTER - Lutskyi, Maksym (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2022)
Purpose: to substantiate the features of innovation development as a priority of state policy of Ukraine and to identify the main ways to build a modern institution of higher education as a research and innovation center. Methods: general and special scientific methods were used to achieve this goal. The use of these methods allowed us to outline the problems of innovative development of modern higher education and science, and the transformation of domestic universities into centers of innovative development. Results: the need to regulate the legal, economic and organizational principles of state regulation of innovation is emphasized. The leading role of the higher education institution as a unique social institution that ensures the creation and development of the intellectual potential of the state is noted. The principles of development of the National Aviation University as an innovation center in the educational and aerospace industry are analyzed, and the main means, methods, and procedures of such development are formulated. The strategic principles of innovative development of the National Aviation University are outlined, the criteria of systematic assessment of its innovative potential are characterized and the basic priorities of development taking into account global challenges are defined. Emphasis is placed on the problems of innovative development of scientific and pedagogical staff in the context of the digitalization of society. Scientific views on modern universities as research and innovation centers are generalized, which provide a unique function of integration of the knowledge society by ensuring interaction with the generation, exchange, and transfer of knowledge. Discussion: problems of innovative development of the system of domestic higher professional education and ways to solve them.